2011
DOI: 10.1007/s11814-010-0425-y
|View full text |Cite
|
Sign up to set email alerts
|

Liquid+liquid equilibria of ternary water+carboxylic acid+solvent systems at 288.15 K

Abstract: The experimental liquid-liquid equilibrium (LLE) data for six ternary systems containing (chloroform+ propionic acid+water), (chloroform+acetic acid+water), (diethyl ether+propionic acid+water), (diethyl ether+acetic acid+water), (trichloroethylene+propionic acid+water) and (trichloroethylene+acetic acid+water) were measured at 288.15 K and at atmospheric pressure. An accurate and simple titration method was used for determining of the concentration of carboxylic acid in the both liquid phases at equilibrium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In order to rationally design and carry out separation operations, such as biological separation and extraction, LLE data are required. Numerous researchers have studied a variety of multicomponent systems, including carboxylic acid–organic solvent–water. , Carboxylic acid separation from aqueous fermentation solutions may benefit from the use of an organic solvent because it is non-toxic to the biological product. In addition, values for the separation factor and distribution coefficient can be calculated from the liquid–liquid equilibrium (LLE) data, allowing for an assessment of the extraction performance.…”
Section: Introductionmentioning
confidence: 99%
“…In order to rationally design and carry out separation operations, such as biological separation and extraction, LLE data are required. Numerous researchers have studied a variety of multicomponent systems, including carboxylic acid–organic solvent–water. , Carboxylic acid separation from aqueous fermentation solutions may benefit from the use of an organic solvent because it is non-toxic to the biological product. In addition, values for the separation factor and distribution coefficient can be calculated from the liquid–liquid equilibrium (LLE) data, allowing for an assessment of the extraction performance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies have investigated liquid–liquid extraction for various kinds of multicomponent systems such as carboxylic acid–organic solvent–water. Organic solvents are noxious for the biological product, and thus organic solvents may be used as a good extraction agent for carboxylic acid separation from aqueous fermentation solutions. In this study, methyl isobutyl ketone (MIBK) was used as a good extraction solvent, which has limited solubility in water and may interact well with carboxylic acid molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have already reported LLE data for the systems consisting of chloroform and carbon tetrachloride. 35−48 Acetone, 35 nicotine 36 acetic acid, 38,46 and tetrahydrofuran 39 were purified using carbon tetrachloride and acetic acid, 37,42,43 while tetrahydrofuran, 39 valeric acid, pyruvic acid, propionic acid, 43 acetyl acetone, 44 and 2-methylaziridine 47 were separated using chloroform. Mixtures of chloroform with other solvents (toluene or diethyl ether) were also used to separate ethanol from water.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, two chlorinated methanes (tri and tetra chloromethane) were chosen as solvents to investigate the liquid–liquid equilibria of ternary systems (water + OPA + chloroform) and (water + OPA + carbon tetrachloride). Some authors have already reported LLE data for the systems consisting of chloroform and carbon tetrachloride. Acetone, nicotine acetic acid, , and tetrahydrofuran were purified using carbon tetrachloride and acetic acid, ,, while tetrahydrofuran, valeric acid, pyruvic acid, propionic acid, acetyl acetone, and 2-methylaziridine were separated using chloroform. Mixtures of chloroform with other solvents (toluene or diethyl ether) were also used to separate ethanol from water. , …”
Section: Introductionmentioning
confidence: 99%